Oral microbiome changes in subjects with obesity following bariatric surgery compared to lean counterparts - Kim, Keun-Suh; Na, Hee Sam; Oh, Tae Jung; Han, Hyejung; Kim, Jiyeon; Hong, Jin-Sil; Lee, Hyo-Jung; Park, Young Suk; Chung, Jin (Frontiers in Microbiology, 2025)
IntroductionThis study aimed to compare oral microbiome profiles between obese and lean individuals without clinical periodontitis, and to assess changes in the oral microbiome of obese subjects following bariatric surgery.MethodsIndividuals with a body mass index (BMI) > 30 were enrolled in the obese group, whereas those with a BMI < 23 served as controls. The obese surgery group, which consented to bariatric surgery, was followed up at 1, 3, and 6 months with clinical examinations. Oral examinations were conducted and periodontal disease was classified based on probing results. Saliva, buccal and subgingival microbiome samples were analyzed for community diversity, relative bacterial abundance, and differential abundance between control (n = 24) and obese group (n = 31). To evaluate effect size and statistical power, we used micropower, a simulation-based method for Permutational Multivariate Analysis of Variance-based β-diversity comparisons.ResultsThe obese group exhibited distinct alpha diversity (buccal: Chao1 p = 0.0002, Shannon p = 0.0003, supragingival: Shannon p < 0.0001) compared with the control group. Bray-Curtis distance analysis indicated significant disparities in microbiome composition distribution in saliva (p = 0.003), buccal (p = 0.002), and subgingival plaque samples (p = 0.001). Although the obese and normal weight groups exhibited no significant periodontal differences, the obese group showed distinct species associated with periodontal disease, especially in subgingival plaque including Filifactor alocis, Peptostreptococcaceae spp., Prevotella spp., and Treponema maltophilum. Cluster analysis of the obese surgery group indicated the emergence of microbiomes associated with a healthy state that increased over time including Streptococcus salivarious and various Veillonella spp., whereas clusters containing periodontal pathogens including Porphyromonas spp., tended to diminish.DiscussionThe oral microbiome at 6 months post-bariatric surgery indicates a potential shift toward a healthy periodontal state, suggesting that weight loss interventions may positively impact oral microbial communities even in the absence of clinical periodontitis.